Technical-economic study for the installation of a processing plant for newsprint using banana raquis. - Paredes Villalta, José Aurelio (Revista Universidad de Guayaquil, 2011)
Install a processing plant newsprint from banana rachis help to reduce the level of imports of the product. To gather information from primary sources: the sample selection, questionnaires, surveys and data processing. For the secondary source was consulted Statistics in specialized national institutions. Market Research found an unmet demand for 3758.755 t. In the Technical Study establishing the balance of lines, material balance, the supply plan, the production plan of the plant capacity to produce up to cover 1194.014 t. The Floor Area of 800 m², were selected machinery and equipment for the production process, where the first annual production will be 900 coils, weighing approximately 1t. For the second year will be of 1,000 coils and from the third year will be of 1,194 coils. Fixed investment reached 246,102.87 and 327,569.49 working capital which will be covered with a 74.26% equity capital and 25.74% financing equivalent to 147,661.72 which is 60% of the fixed investment. The unit costs of product is located at 363.97, coming to set the selling price 583.00 with a utility to distribute 23.95% of total sales. Total investment is set at 576,110.77. Mixed TMAR project is 18.66%. A VPN of 122,453.29 and a TIR of 23.80%. Sensitivity Analysis shows that even sales down to 4.31% and rising production costs by up to 11.58% can still make the investment.